A birth of bipartite exon by intragenic deletion. Issue 3 (1st March 2017) - Nozu, Kandai; Iijima, Kazumoto; Igarashi, Toru; Yamada, Shiro; Kralovicova, Jana; Nozu, Yoshimi; Yamamura, Tomohiko; Minamikawa, Shogo; Morioka, Ichiro; Ninchoji, Takeshi; Kaito, Hiroshi; Nakanishi, Koichi; et al.
Abstract: Background: Disease‐causing mutations that activate transposon‐derived exons without creating a new splice‐site consensus have been reported rarely, but they provided unique insights into our understanding of structural motifs required for inclusion of intronic sequences in mature transcripts. Methods: We employ a combination of experimental and computational techniques to characterize the first de novo bipartite exon activation in genetic disease. Results: The exon originated from two separate introns as a result of an in‐frame COL4A5 deletion associated with a typical Alport syndrome. The deletion encompassed exons 38 through 41 and activated a cryptic 3′ and 5′ splice site that were derived from intron 37 and intron 41, respectively. The deletion breakpoint was in the middle of the new exon, with considerable complementarity between the two exonic parts, potentially bringing the cryptic 3′ and 5′ splice site into proximity. The 3′ splice site, polypyrimidine tract and the branch site of the new exon were derived from an inactive, 5′ truncated LINE‐1 retrotransposon. This ancient LINE‐1 copy sustained a series of mutations that created the highly conserved AG dinucleotide at the 3′ splice site early in primate development. The exon was fully included in mature transcripts and introduced a stop codon in the shortened COL4A5 mRNA, illustrating pitfalls of inferring disease severity from DNA mutation alone. Conclusion: These results expand the repertoire of mutational mechanisms that alter RNA processing in genetic disease and illustrate the extraordinary versatility of transposed elements in shaping the new exon‐intron structure and the phenotypic variability. Abstract : We describe the first case of bipartite exon activation in human genetic disease. The new exon was activated by a large intragenic deletion that brought complementary sequences of two separate introns into proximity, including a LINE‐1‐derived 3′ splice site, polypyrimidine tract and branch site. We also identify cis‐elements required for this LINE‐1 exonization and putative RNA structures and trans‐acting factors contributing to inclusion of the fusion exon in mature transcripts. This case illustrates an unexpected complexity of mutational mechanisms contributing to the phenotypic variability, expands the spectrum of currently known LINE‐1‐mediated morbidities and highlights the extraordinary versatility of transposed elements in shaping the new exon‐intron structure.